Organ-Specific Endothelial Dysfunction Following Total Body Irradiation Exposure - Guru Prasad Sharma; Heather A. Himburg (Toxics, 2022)
As the single cell lining of the heart and all blood vessels, the vascular endothelium serves a critical role in maintaining homeostasis via control of vascular tone, immune cell recruitment, and macromolecular transit. For victims of acute high-dose radiation exposure, damage to the vascular endothelium may exacerbate the pathogenesis of acute and delayed multi-organ radiation toxicities. While commonalities exist between radiation-induced endothelial dysfunction in radiosensitive organs, the vascular endothelium is known to be highly heterogeneous as it is required to serve tissue and organ specific roles. In keeping with its organ and tissue specific functionality, the molecular and cellular response of the endothelium to radiation injury varies by organ. Therefore, in the development of medical countermeasures for multi-organ injury, it is necessary to consider organ and tissue-specific endothelial responses to both injury and candidate mitigators. The purpose of this review is to summarize the pathogenesis of endothelial dysfunction following total or near total body irradiation exposure at the level of individual radiosensitive organs.